Covıd-19: Fınancıal Spıllover To Emergıng Asıa’s Fınancıal Markets - Susilo, Chandra; Hendranastiti, Nur Dhani (APMBA (Asia Pacific Management and Business Application), 2022)
This paper aims to investigate the role of China compared to the US in transmitting spillover to ASEAN-5 countries (or vice versa) during COVID-19 recession. It uses the DECO GARCH model of Engle & Kelly (2012) to see the dynamic correlation between indexes and the spillover index by Diebold and Yilmaz (2012) to describe the direction of spillover between countries. This paper analyzes daily return data on stock market indexes of China, the United States, and ASEAN-5 for the period 2016 to 2022. The findings demonstrate an increase in positive spillover correlation during the COVID-19 crisis between China and ASEAN-5 as well as US and ASEAN-5 albeit with lower pre crisis correlation level than China. US acts as a net transmitter (spillover to ASEAN-5 is higher than in the opposite direction), while China is a net receiver. The findings are beneficial to provide insight into Emerging Asia marketâ€™s connectedness, which in turn will be able to guide the hedging strategies and portfolio risk management of investment in the region. Â